Análise biomecânica em operadores de checkout: avaliação de dor e desconforto dos operadores de caixa de uma rede de supermercado na cidade de Araguaína-TO - Rocha, Maicon Junio Oliveira (2024)
The Industrial Revolution brought significant advancements to production and other societal segments, including the supermarket sector. Checkout operators, who work long hours seated, face health risks such as visual fatigue, stress, and musculoskeletal injuries. Studies highlight ergonomic issues such as repetitiveness and inadequate posture. Regulatory Norms (NR) have been established to improve working conditions, particularly NR 17, which focuses on ergonomics. This research focuses on the biomechanical analysis of operators, addressing ergonomics to prevent injuries and improve workers' well-being. The objective of this study was to assess musculoskeletal pain and discomfort among checkout operators in a supermarket chain in the city of Araguaína-TO, with a sample comprising 36 operators of both sexes, all with at least 12 months of experience in the position. The research was approved by the Ethics Committee of the Federal Institute of Tocantins and authorized by the supermarket chain's management. The theoretical foundation centers on research related to the ergonomics of checkout operators, as well as the tools that will be used in biomechanical analysis. This research is classified as applied, bibliographic, descriptive, and exploratory. The tools used for the analysis include the Nordic Musculoskeletal Symptoms Questionnaire (NMQ), the Rapid Upper Limb Assessment (RULA), and the Occupational Repetitive Actions (OCRA). The results demonstrate musculoskeletal pain among checkout operators, particularly in the upper back and wrists, which are the most affected areas. The analysis revealed the need for ergonomic interventions to reduce inadequate postures and repetitive movements, aiming to promote safer biomechanical conditions in the workplace.